2006
DOI: 10.1007/s11192-006-0124-y
|View full text |Cite
|
Sign up to set email alerts
|

Proceedings literature as additional data source for bibliometric analysis

Abstract: Scientific meetings have become increasingly important channels for scholarly communication. In several fields of applied and engineering sciences they are -according to the statements of scientists active in those fields -even more important than publishing in periodicals. One objective of this study is to analyse the weight of proceedings literature in all fields of the sciences, social sciences and humanities as well as the use of the ISI Proceedings database as additional data source for bibliometric studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 10 publications
2
46
0
Order By: Relevance
“…It must be noted that in some fields, such as computer science, publishing focuses primarily on conferences and certain conferences are even more valued publishing channels than scientific journals (e.g. Glänzel et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…It must be noted that in some fields, such as computer science, publishing focuses primarily on conferences and certain conferences are even more valued publishing channels than scientific journals (e.g. Glänzel et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion this fourth category is well covered in ''final product''. Glänzel et al (2005) found, based on data extracted from the 1994-2002 volumes of the ISI Proceedings database's Science and Technology edition, that about half of the papers indexed there belonged to the field of engineering. In their categorization, computer science is viewed as part of engineering.…”
Section: Literature Reviewmentioning
confidence: 99%
“…International co-authorship is in general accepted as a basically positive phenomenon. Severe political and economic changes as observed, for instance, in the economies in transitions in Eastern Europe and new members of the European Union have a strong influence on collaboration patterns [GLÄNZEL & SCHLEMMER, 2006]. Thus, extensive collaboration might also be used as means for compensation for the negative financial effects which have hit the basic research system of several EastEuropean countries before and after the political and economical changes of the nineties [BRAUN & GLÄNZEL, 1996].…”
Section: International Co-authorship Linksmentioning
confidence: 99%